INOVASI PEMBELAJARAN PIDATO DENGAN PEMODELAN BERBASIS GOOGLE SITES WUJUD OPTIMALISASI LITERASI DIGITAL DALAM MERDEKA BELAJAR - Tri Murniati (Universitas Terbuka, 2022)
This research started from speech learning that was not maximal. A Google site-based model was chosen as the solution. Therefore, it is hoped that the learning process will be varied through Google Sites in the form of recordings and could be viewed any time. The objectives were to describe the process of applying Google Sites-based modeling in speech learning, and to describe the application of Google Sites-based modeling to improve students’ speaking ability. The method used was classroom action research, which included four research stages, namely planning, implementing, observing, and reflecting. Observation and tests were used as data collection techniques and were analyzed quantitatively and qualitatively. The pre-cycle result showed the average score was 61.13, Cycle I’s average was 75.31, and Cycle II was 80.25. In conclusion, the result of this research showed that Google site-based modeling could improve students’ speaking ability.